(untitled) (Diametros, 2005)
The concept of God refers to the being infinite, self-contained, transcendent to the world, necessary, omnipotent, unique, and personal. Because there is no valid proof that such concept is incoherent, we can presume that it is coherent. Then it is possible to start the rational discussion whether the concept has real referent. Among four possible positions concerning the existence of God (theism, atheism, agnosticism and skepticism) the skepticism makes the fewest theoretical troubles. All attempts to justify theism (the sentence “God exists” is true) presuppose the conclusion (to accept the premises of the argument for theism, we need to accept the conclusion of the argument). The similar troubles concern atheism (the sentence “God does not exist” is true). Agnosticism (we do not know and we will never know neither that God exists, nor that God does not exist) is not justified (we do not know does not entail that we will never know in the future). That is why we should say that the most justified position concerning the existence of God is skepticism: we do not know which of the three (theism, atheism or agnosticism) is true or more probable than others. Skepticism concerning the existence of God is not global but local (limited to our present knowledge of the existence/nonexistence of God).